SEASONAL AND INTRA-SEASONAL VARIABILITY OF OCEAN THERMAL POTENTIAL ENERGY IN THE INDONESIAN EXCLUSIVE ECONOMIC ZONE - Suprijo, Totok; Napitupulu, Gandhi; Ningsih, Nining Sari; Sinaga, Denny Basardo Jonatan; Rachman, Audi (Marine Geological Institute of Indonesia, 2024)
Ocean thermal energy is a promising marine renewable energy resource that can be developed as a clean energy alternative for Indonesia, which is in the equatorial or tropical region. This study assesses the potential of ocean thermal energy as a renewable energy source in the Indonesian Exclusive Economic Zone (EEZ) by estimating the monthly, seasonal, and intra-seasonal variability of ocean thermal energy conversion (OTEC) resources. The Indonesian EEZ spans from 6°N to 11°S and 95°E to 139°E, covering an area of 3,495,698.72 km². Using temperature data from simulations of the Hybrid Coordinate Ocean Model (HYCOM), the study evaluates the potential of OTEC resources over a 50-year period (from January 1964 to December 2013) with a spatial resolution of 0.125°. Estimation of OTEC potential power resources was based on temperature differences at depths of 20 m and 1000 m, following the hybrid cycle working principle.The results of the estimations indicate that the area has a monthly average potential power of 289.73 GW. The estimation also reveals seasonal and intra-seasonal variability in this potential energy, with fluctuations ranging from 280.09 GW in August to 295.65 GW in December, influenced by phenomena such as ENSO (El Niño Southern Oscillation) and IOD (Indian Ocean Dipole). In the Indonesian EEZ, the average potential thermal power decreases to 288.23 GW during an El Niño event and increases to 291.72 GW during a La Niña event. The IOD phenomenon has a similar effect, with potential decreasing to 281.82 GW during a positive IOD event and rising to 292.64 GW during a negative IOD event.